1975
DOI: 10.1172/jci108137
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in serum immunoreactive parathyroid hormone in rats and in parathyroid hormone secretion in vitro by 1,25-dihydroxycholecalciferol.

Abstract: A B S T R A C T The present study determined the effects of 1,25-dihydroxycholecalciferol on serum immunoreactive parathyroid hormone and on parathyroid hormone secretion in vitro. Rats injected i.p. with 1,25-dihydroxycholecalciferol, 130 pmol (2 U)/140 g body wt, which is probably a physiologic dose, had a significant 43% decrease in serum immunoreactive parathyroid hormone at 4 h. In addition, this dose of 1,25-dihydroxycholecalciferol inhibited the serum immunoreactive parathyroid hormone response to hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(50 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…Active vitamin D 3 and its analogues such as calcitriol and alfacalcidol are potent suppressors of PTH synthesis and secretion by parathyroid cells [20,21]. Alfacalcidol also decreased serum PTH levels in the PHP patients in this study, and similar results were observed in previous studies [11,19,22].…”
Section: +supporting
confidence: 91%
“…Active vitamin D 3 and its analogues such as calcitriol and alfacalcidol are potent suppressors of PTH synthesis and secretion by parathyroid cells [20,21]. Alfacalcidol also decreased serum PTH levels in the PHP patients in this study, and similar results were observed in previous studies [11,19,22].…”
Section: +supporting
confidence: 91%
“…According to the results shown in Fig. 1 Several studies suggest that 1 ,25(OH)2D3 directly inhibits the secretion of PTHfrom the parathyroid glands (22)(23)(24)(25) and also suppresses the production of PTHmRNA in parathyroid glands, independent of the concentration of ionized Ca (26)(27)(28). In the present study, the weekly administration of 8.0 |Ug of 1,25(OH)2D3 suppressed the PTH level without elevating the serum Ca.…”
Section: Discussionsupporting
confidence: 65%
“…Serum immunoreactive parathyroid hormone (iPTH) was measured using an antiserum (chick 12) directed against the carboxy terminus of the PTH molecule (24). Creatinine clearance was calculated using the conventional formula for clearance.…”
Section: Methodsmentioning
confidence: 99%